Bricks and Tiles as Lived Objects at Jesuit Missions - Lenik, Stephan T. (US catholic historian, 2025)
Material culture and architecture have played an important role in sustaining Catholic communities in the United States and globally. Archaeologists' discussions of institutions emphasize how material objects contribute to institutions across time and space by providing the permanence and simplicity of message which can work across cultures. The material manifestations of the Catholic Church can be divided into sacred "inscribed" objects and common, everyday "lived" objects. This paper considers the role of "lived" objects in maintaining social control at missions by looking to archaeological evidence of ceramic architectural materials, specifically bricks and tiles, from English Jesuit missions in Maryland and French Jesuit missions in the Caribbean and South America from the seventeenth to the twentieth century. Bricks and tiles typically occur in repeatable forms with subtle variations in appearance, color, and texture and are preserved in the archaeological record. Approaching these material culture types through a comparative study in two regions considers how architectural materials contributed to the durability of the Church as these objects enabled both commonality and variation across Catholic mission properties.